ICT Skill in Administration: Employing Electronic Achieve Application in Archive practice Course Higher Education - Edy Suryanto; Nina Oktarina; Margunani Margunani; Rusdarti Rusdarti (Journal of Educational Science and Technology (EST), 2023)
Today's young generation is used to learning with integrated technology (ICT). Technology-based learning (ICT) is essential in supporting the preparation of prospective pre-service teacher to be creative and innovative according to future needs. Through this paper, we investigate how the impact of using the E-Archive application is supported by a simulation of a contextual approach to archiving skills. The researcher adopted an experimental research method with two groups (experimental; control) with a posttest; to determine the impact of the proposed contextual approach using the E Archive application on archiving skills. The sample in this study consisted of 86 pre-service teacher students, divided into two experimental and control groups. The intervention is carried out in simulations using ICT applications, which have a more beneficial impact on improving student skills than conventional approaches. Data was collected through pretest and posttest, which were analyzed and processed statistically. The results of parametric statistical analysis show that students in the experimental class have superior skills compared to controls. They are more familiar with and actively involved in archival simulations and perform better using ICT with contextualized simulations. Suggestions for improving skills should be made by considering technological developments and selecting the right approach.